2011
DOI: 10.1007/s11916-011-0186-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Hyperexcitability: A Substrate for Central Neuropathic Pain After Spinal Cord Injury

Abstract: Neuronal hyperexcitability produces enhanced pain transmission in the spinal dorsal horn after spinal cord injury (SCI). Spontaneous and evoked neuronal excitability normally are well controlled by neural circuits. However, SCI produces maladaptive synaptic circuits in the spinal dorsal horn that result in neuronal hyperexcitability. After SCI, activated primary afferent neurons produce enhanced release of glutamate, neuropeptides, adenosine triphosphate, and proinflammatory cytokines, which are known to be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 48 publications
2
60
0
Order By: Relevance
“…However, we and others consistently reported that bilateral spinal cord injuries, such as spinal contusion injury, produce mechanical allodynia in both hindpaws, and hyperexcitability of spinal dorsal horn neurons and thalamic VPL neurons, suggesting that STTs, and not DC-MLs, are critical contributors to neuropathic pain following spinal contusion injury. 27,28 Taken together, the present data suggest that the intact (contralateral) side of the spinal dorsal horn mediates bilaterally-enhanced nociceptive transmissions to the gracile regions, which result in mechanical allodynia in the hindpaws and hyperexcitability of the gracile neurons following spinal hemisection. 29 However, the neuroanatomical and neurochemical changes in both the supraspinal regions and gracile neurons following spinal hemisection require further study.…”
Section: Figsupporting
confidence: 56%
“…However, we and others consistently reported that bilateral spinal cord injuries, such as spinal contusion injury, produce mechanical allodynia in both hindpaws, and hyperexcitability of spinal dorsal horn neurons and thalamic VPL neurons, suggesting that STTs, and not DC-MLs, are critical contributors to neuropathic pain following spinal contusion injury. 27,28 Taken together, the present data suggest that the intact (contralateral) side of the spinal dorsal horn mediates bilaterally-enhanced nociceptive transmissions to the gracile regions, which result in mechanical allodynia in the hindpaws and hyperexcitability of the gracile neurons following spinal hemisection. 29 However, the neuroanatomical and neurochemical changes in both the supraspinal regions and gracile neurons following spinal hemisection require further study.…”
Section: Figsupporting
confidence: 56%
“…Central sensitization of second order spinothalamic tract (STT) neurons in the superficial laminae of the dorsal horn is one major mechanism implicated in the pathogenesis of neuropathic pain (Gwak and Hulsebosch, 2011b). These changes can be chronic, resulting in the persistence of neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperexcitability of dorsal horn pain projection neurons (“central sensitization”) is a major substrate for neuropathic pain following SCI (Gwak and Hulsebosch, 2011b). This includes decreased threshold for activation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Neuron hyper-excitability is an essential component of many disorders of the central nervous system (Curatolo et al, 2001), and also plays a role in the molecular basis of addiction (Koob & Le Moal, 2001) and autoimmune disorders (Hart et al, 2002). In particular, it produces enhanced pain transmission in the spinal dorsal horn after spinal cord injury (Gwak & Hulsebosch, 2011). Recently, the SK3 ion channel has gained attention as a new therapeutic target for disorders involving neuron hyper-excitability (Schlichter et al, 2010).…”
Section: Potential Host Receptors Of Na-asp-2mentioning
confidence: 99%